Risk of stroke and oral anticoagulant use in atrial fibrillation: a cross-sectional survey. - Holt, T; Hunter, T; Gunnarsson, C; Khan, N; Cload, P; Lip, G (2012)
BACKGROUND: Oral anticoagulants substantially reduce the risk of stroke in atrial fibrillation but are underutilised in current practice. AIM: To measure the distribution of stroke risk in patients with atrial fibrillation (using the CHADS(2) and CHA(2)DS(2)-VASc scores) and changes in oral anticoagulant use during 2007-2010. DESIGN AND SETTING: Longitudinal series of cross-sectional survey in 583 UK practices linked to the QResearch(®) database providing 99 351 anonymised electronic records from people with atrial fibrillation. METHOD: The proportion of patients in each CHADS(2) and CHA(2)DS(2)-VASc risk band in 2010 was calculated; for each of the years 2007-2010, the proportions with risk scores ≥2 that were using anticoagulants or antiplatelet agents were estimated. The proportions identified at high risk were re-estimated using alternative definitions of hypertension based on coded data. Finally, the prevalence of comorbid conditions in treated and untreated high-risk (CHADS(2) ≥2) groups was derived. RESULTS: The proportion at high risk of stroke in 2010 was 56.9% according to the CHADS(2) ≥2 threshold, and 84.5% according to CHA(2)DS(2)-VASc ≥2 threshold. The proportions of these groups receiving anticoagulants were 53.0% and 50.7% respectively and increased during 2007-2010. The means of identifying the population of individuals with hypertension significantly influenced the estimated proportion at high risk. Comorbid conditions associated with avoidance of anticoagulants included history of falls, use of nonsteroidal anti-inflammatory drugs, and dementia. CONCLUSION: Oral anticoagulant use in atrial fibrillation has increased in UK practice since 2007, but remains suboptimal. Improved coding of hypertension is required to support systematic identification of individuals at high risk of stroke and could be assisted by practice-based software.